2012
DOI: 10.1258/acb.2011.011219
|View full text |Cite
|
Sign up to set email alerts
|

Extreme hyperferritinaemia: further considerations

Abstract: Extreme hyperferritinaemia: further considerationsIn their case report, Sami et al. 1 state that very high ferritin concentrations (greater than 10,000 mg/L) have only been described in adult Still's disease, multiple blood transfusions and severe acute hepatocellular damage. It may be of interest to the authors that such marked hyperferritinaemia has also been documented in patients with the human immunodeficiency virus (HIV) complicated by superinfection with a range of opportunistic organisms, particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Most of the previous studies either defined primary diagnosis as a single cause or allowed multiple diseases as causes of hyperferritinemia [8][9][10][11][13][14][15][16]. Our observation that 41% of the patients with hyperferritinemia had multiple underlying causes indicated that, together with reports showing that 16.8-46% of patients with hyperferritinemia had more than one etiology, either approach was not satisfactory to elucidate the etiologies of hyperferritinemia encountered in the clinical setting [8,13,17].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Most of the previous studies either defined primary diagnosis as a single cause or allowed multiple diseases as causes of hyperferritinemia [8][9][10][11][13][14][15][16]. Our observation that 41% of the patients with hyperferritinemia had multiple underlying causes indicated that, together with reports showing that 16.8-46% of patients with hyperferritinemia had more than one etiology, either approach was not satisfactory to elucidate the etiologies of hyperferritinemia encountered in the clinical setting [8,13,17].…”
Section: Discussionmentioning
confidence: 80%
“…As the range of the serum ferritin level is wide without upper limit but the ferritin elevation was mild or modest in many patients, it appeared clinically important and useful to study the characteristics of marked hyperferritinemia. Previous studies of a relatively small number of patients which determined a primary cause as the etiology reported that either chronic transfusion or malignancy was the most frequent cause of marked hyperferritinemia [9][10][11]15]. One large study which similarly determined a primary cause reported hematological malignancy to be the most common cause followed by liver failure, HLH, and infection [12].…”
Section: Discussionmentioning
confidence: 99%
“…Thurlow et al 1 describe two novel mutations in the L-ferritin coding sequence associated with benign hyperferritinaemia showing abnormal ferritin glycosylation. Marshall et al 2 discuss causes of extreme hyperferritinaemia ( plasma ferritin concentration .10,000 mg/L).…”
mentioning
confidence: 99%
“…Marshall et al . 2 discuss causes of extreme hyperferritinaemia (plasma ferritin concentration >10,000 μ g/L).…”
mentioning
confidence: 99%